Conceptual metaphors denoting "Anger" in the dailystar.co.uk and cand.com.vn (2012-2013) from cognitive semantics - Tran, Thi Minh Yen (ĐHNN, 2017)
Metaphor, especially conceptual metaphor, is a cognitive device for humans to conceptualize abstract domains. Having chosen Lakoff and Johnson's Conceptual Metaphor Theory as the analytical framework, 77 samples from English and Vietnamese newspapers were analyzed to address how conceptual metaphors for anger work in English and Vietnamese newspapers as well as indicate the similarities and differences between English and Vietnamese in terms of those conceptual metaphors. It aims to enhance the effectiveness of teaching, learning and understanding conceptual metaphors in English and Vietnamese. Within the limit of a brief research, the author expect that the two languages -English and Vietnamese - which express the conceptual metaphors involved will reveal some different features of the two cultures.